PENINGKATAN KUALITAS KEMENYAN DENGAN MENGGUNAKAN PELARUT ORGANIK - Bambang Wiyono (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
This experiment is intended to improve the quality of the several types of benzoin by using an aceton solvent. The benzoin consisted of four samples with decreasing order of quality: